Analysis of the aerodynamic characteristics of an ejection seat system using computational fluid dynamics - Rahman, Md. Mahbubur; Prakash, Ved; Chandel, Sunil; Thakur, D. G.; Čep, Robert; Khedkar, Nitin; Salunkhe, Sachin; Abouel Nasr, Emad S. (Frontiers in Mechanical Engineering, 2023)
In the present work, an investigation of the aerodynamic characteristics of an ejection seat occupant is carried out using the commercially available computational fluid dynamics software ANSYS Fluent. 3D Reynolds-averaged Navier–Stokes equations are solved to obtain the aerodynamic coefficients of the ejection seat system. For this analysis, an unstructured grid is generated for the ejection seat occupant using ANSYS meshing. Validation is carried out and the performance of three different turbulence models is analyzed at Mach 0.6. Based on the most suitable turbulence model, further analysis of the aerodynamic coefficients of the ejection seat occupant is calculated at Mach numbers of 0.35, 0.45, 0.55, 0.65, and 0.75. For all values of Mach, the angle of attack is varied from −15° to 15° in 5° increments and the yaw angle is varied from 0° to 60° in 10° increments. Based on the results, it is observed that the magnitude of the axial force decreases with increasing angle of attack and yaw angle. Similarly, the normal force coefficient and pitching moment coefficient decrease with increasing angle of attack. Finally, the side force coefficient, yawing moment, and rolling moment coefficients increase with increasing yaw angle.